The transcription factor NF-Kappa B: an evolutionarily conserved mediator of immune and inflammatory responses - Ghosh, Sankar (Henry Stewart Talks, 2007)
NF-kappa B activation and function, Signal transduction pathway, Mechanism of post-transcriptional induction, Gene activation, Role of NF-kappa B in physiological processes, Initiation of the immune system, Cell survival
Updated at 2015/08/31, Archived at 2022/04/13